Experimental and numerical analysis of a methane thermal decomposition reactor. (5th October 2017) - Paxman, D.; Trottier, S.; Flynn, M.R.; Kostiuk, L.; Secanell, M.
Abstract: An indirectly heated tubular reactor is fabricated and used to study methane thermal decomposition conversion and determine kinetic parameters. A combined perfectly mixed reactor with bypass (CPMR) is proposed as an alternative to the traditional perfectly mixed and plug flow reactors. The CPMR model is used in order to account for buoyancy flow in the reactor. Results comparing the numerical predictions from all three models to experimental data show that buoyancy effects are significant in the reactor under study and also in most reactors in the literature. Including this effect might significantly improve the accuracy of the model predictions. The CPMR reactor model with a reaction rate constant of 5.43 × 10 15 1/s and an activation energy of 420.7 kJ/mol is capable of reproducing the obtained experimental data in this study and in the literature. Graphical abstract: Highlights: An indirectly heated methane thermal decomposition tubular reactor is fabricated. A numerical model is proposed for reactors where buoyancy effects are significant. Kinetic parameters are obtained and compared to previous result in literature. The numerical model is capable of predicting appropriate kinetic parameters.